Drammaturgia e metamorfosi del genio maligno: Soggetti e spettri tra follia e ragione - Chiafari, Rosanna (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
The aim of this work is to come into the debate of “cogito” that Michael Foucault and Jacques Derrida have put in scene during the second half of twentieth century, starting by their respective readings of the Cartesian text. To get straight into the heart of the matter, there are three original and unusual points of view that we would like to rais: the first is a particular condition of the history’s concept; the second is the role of Freud’s psychoanalysis in the general economy of Foucault’s work; the last one, it’s about the relationship between philosophy and literature. Walking down these three runs, we would like to prove that every process of subjectivation redefines the borders of human being and affects the subject also in his peripheral structures.